Predictors of Long‐term Clinical Endpoints in Patients With Refractory Angina. Issue 2 (30th January 2015) - Povsic, Thomas J.; Broderick, Samuel; Anstrom, Kevin J.; Shaw, Linda K.; Ohman, E. Magnus; Eisenstein, Eric L.; Smith, Peter K.; Alexander, John H.
Abstract : Background: Clinical outcomes in patients with refractory angina (RA) are poorly characterized and variably described. Using the Duke Database for Cardiovascular Disease (DDCD), we explored characteristics that drive clinical endpoints in patients with class II to IV angina stabilized on medical therapy. Methods and Results: We explored clinical endpoints and associated costs of patients who underwent catheterization at Duke University Medical Center from 1997 to 2010 for evaluation of coronary artery disease (CAD) and were found to have advanced CAD ineligible for additional revascularization, and were clinically stable for a minimum of 60 days. Of 77 257 cardiac catheterizations performed, 1908 patients met entry criteria. The 3‐year incidence of death; cardiac rehospitalization; and a composite of death, myocardial infarction, stroke, cardiac rehospitalization, and revascularization were 13.0%, 43.5%, and 52.2%, respectively. Predictors of mortality included age, ejection fraction (EF), low body mass index, multivessel CAD, low heart rate, diabetes, diastolic blood pressure, history of coronary artery bypass graft surgery, cigarette smoking, history of congestive heart failure (CHF), and race. Multivessel CAD, EF<45%, and history of CHF increased risk of mortality; angina class and prior revascularization did not. Total rehospitalization costs over a 3‐year period per patient were $10 185 (95% CI 8458, 11912) in 2012 US dollars. Conclusions: Clinically stable patients with RA who are medically managed have a modest mortality, but a high incidence of hospitalization and resource use over 3 years. These findings point to the need for novel therapies aimed at symptom mitigation in this population and their potential impact on health care utilization and costs.